Dose dependency of γ‐H2AX formation in the rat urinary bladder treated with genotoxic and nongenotoxic bladder carcinogens. Issue 9 (23rd March 2020) - Yamada, Takanori; Toyoda, Takeshi; Matsushita, Kohei; Morikawa, Tomomi; Ogawa, Kumiko
Abstract: We previously reported that immunostaining for γ‐H2AX, a biomarker of DNA damage, in the rat urinary bladder is useful for early detection of bladder carcinogens in 28‐day toxicity studies. Here, we aimed to examine the dose dependency of γ‐H2AX formation in the urinary bladder of rats. Male F344 rats (aged 6 weeks) were orally administered N ‐butyl‐ N ‐(4‐hydroxybutyl)nitrosamine (BBN; 0%, 0.0001%, 0.001%, 0.01%, 0.02%, or 0.05% in drinking water), a genotoxic bladder carcinogen, and melamine (0%, 0.3%, 1.0%, or 3.0% in the diet), a nongenotoxic bladder carcinogen, for 2 days or 4 weeks. Immunohistochemical analysis showed that γ‐H2AX‐ and Ki67‐positive epithelial cells in the bladder urothelium were significantly increased, with a clear dose dependency, in both BBN‐ and melamine‐treated groups. Additionally, γ‐H2AX formation was detected from the lower‐dose group, without increased Ki67 expression or histopathologic findings. The ratios of γ‐H2AX‐positive cells at week 4 in both BBN‐ and melamine‐treated groups were higher than those on day 2, indicating the time‐dependent increase in γ‐H2AX formation. Immunofluorescence double‐staining revealed that γ‐H2AX single‐positive cells without Ki67 expression were often found in the urothelium of BBN‐treated rats, whereas most γ‐H2AX‐positive cells were Ki67‐positive in the melamine group. Our results demonstrated that γ‐H2AX formation in the urinary bladder increased in a clear dose‐dependent manner and that γ‐H2AX immunostaining has the potential to detect bladder carcinogens after a 2‐day administration. Furthermore, the association of genotoxic mechanisms in bladder carcinogenesis could be determined by analyzing the colocalization of γ‐H2AX and Ki67 in the urothelium. Abstract : We examined the dose dependency of γ‐H2AX formation in the urinary bladder of rats treated with multiple doses of BBN, a genotoxic bladder carcinogen, and melamine, a nongenotoxic bladder carcinogen, for 2 days or 4 weeks. γ‐H2AX formation at both periods was significantly increased with a clear dose dependency in the BBN‐ and melamine‐treated groups. Our results suggest the possibility that the association of genotoxic mechanisms in bladder carcinogenesis could be determined by analyzing the colocalization of γ‐H2AX and Ki67.